2014
DOI: 10.1007/s11255-014-0650-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein-energy wasting, as well as overweight and obesity, is a long-term risk factor for mortality in chronic hemodialysis patients

Abstract: We showed that low values of SGA, nPNA, and PhA independently predict mortality in HD patients. In conjunction with an earlier study, we demonstrated that the relative risk of death associated with these markers is highest during the first year of monitoring and it decreases in the following 4 years, although it still remains significantly increased. On the other hand, overweight and obesity were also associated with lower survival after 5 years, whereas this association was not apparent after 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 45 publications
5
38
1
4
Order By: Relevance
“…Overall, per year increase in age the HR increased by 3%, by 4% in men and by 2% in women. This applied similarly to patients with longer and shorter duration of diabetes mellitus and is in accordance with previously reported survival analyses conducted in dialysis collectives [5, 6, 10-13]. Our results extend these findings to a purely diabetic patient collective with a median follow-up time of 11.5 years.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, per year increase in age the HR increased by 3%, by 4% in men and by 2% in women. This applied similarly to patients with longer and shorter duration of diabetes mellitus and is in accordance with previously reported survival analyses conducted in dialysis collectives [5, 6, 10-13]. Our results extend these findings to a purely diabetic patient collective with a median follow-up time of 11.5 years.…”
Section: Discussionsupporting
confidence: 92%
“…This is even more so because the combination of diabetes and end stage renal disease increases the cardiovascular risk dramatically [4]. Even though there are many studies trying to predict survival of dialysis patients according to single risk factors, there are only few doing so in diabetic dialysis patients and with a systematic range of factors potentially characterizing survivors [4-6] and none for long-term survival (>10 years), a large patient collective and specific subgroups. However, such analyses might enable clinicians to estimate their patients’ mortality risk, to identify and minimize individual risk factors, to promote protective factors, and, as a result, to further personalize their treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In large population studies, overweight, low body cell mass and phase angle have shown to increase morbidity and mortality 18,19 . However, in patients with end-stage renal disease, an "obesity paradox" has been consistently reported: High BMI is associated with lower all-cause mortality 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A perda de função renal provoca diversas alterações metabólicas, sendo a desnutrição energético-proteica (DEP) um dos distúrbios mais prevalentes em pacientes com DRC em hemodiálise, estando relacionada com o aumento das taxas de morbidade e mortalidade. Sua etiologia é multifatorial e inclui aspectos relacionados tanto ao consumo alimentar insuficiente em energia e nutrientes quanto às alterações hormonais e metabólicas que podem ocasionar um aumento do catabolismo energético e/ou proteico, como perda de nutrientes pelo dialisato, bioincompatibilidade das membranas dos filtros de diálise, resistência à ação da insulina e do hormônio do crescimento, acidose metabólica, presença de comorbidades e inflamação 5 , fazendo com que a avaliação nutricional seja de extrema importância no tratamento desses pacientes, sendo ideal a utilização de diferentes formas para essa avaliação 6 . Nesse sentido, a utilização da espessura do músculo adutor do polegar (EMAP) é uma medida que passou recentemente a ser utilizada como marcador devido a ser facilmente aferida, além de não ser influenciada pelo estado hídrico 7 , sendo que alguns estudos demonstraram que a mesma é um bom marcador do estado nutricional em pacientes com DRC 8,9 .…”
Section: Introductionunclassified